Extrapolation, interpolation, and smoothing of stationary time series : with engineering applications - Wiener, Norbert (Cambridge : Technology Press of the Massachusetts Institute of Technology, 1949)
Extrapolation, interpolation, and smoothing of stationary time series represents the the theory pertaining to methods and techniques in the design of communication systems.
lje 23/1/19
Loans
Keywords: Time-series analysis; Time series